Building telephony systems with OpenSER : a step-by-step guide to building a high-performance telephony system - Goncalves, Flavio E., 1966- (Packt Pub., 2008)
This book teaches how to develop a fast and flexible Session Initiation Protocol (SIP) server using OpenSER and shows how OpenSER can be used to implement features not available in Asterisk PBX. This book is for readers who want to understand how to build a SIP provider from scratch using OpenSER. Telephony and Linux experience will be helpful but is not essential. Readers need not have prior knowledge of OpenSER.